Hybrid Shape Memory Alloy-Based Nanomechanical Resonators for Ultrathin Film Elastic Properties Determination and Heavy Mass Spectrometry - Stachiv, Ivo; Gan, Lifeng (Materials (Basel, Switzerland), 2019)
Micro-/nanomechanical resonators are often used in material science to measure the elastic properties of ultrathin films or mass spectrometry to estimate the mass of various chemical and biological molecules. Measurements with these sensors utilize changes in the resonant frequency of the resonator exposed to an investigated quantity. Their sensitivities are, therefore, determined by the resonant frequency. The higher resonant frequency and, correspondingly, higher quality factor (Q-factor) yield higher sensitivity. In solution, the resonant frequency (Q-factor) decreases causing a significant lowering of the achievable sensitivity. Hence, the nanomechanical resonator-based sensors mainly operate in a vacuum. Identification by nanomechanical resonator also requires an additional reference measurement on the identical unloaded resonator making experiments, due to limiting achievable accuracies in current nanofabrication processes, yet challenging. In addition, the mass spectrometry by nanomechanical resonator can be routinely performed for light analytes (i.e., analyte is modelled as a point particle). For heavy analytes such as bacteria clumps neglecting their stiffness result in a significant underestimation of determined mass values. In this work, we demonstrate the extraordinary capability of hybrid shape memory alloy (SMA)-based nanomechanical resonators to i) notably tune the resonant frequencies and improve Q-factor of the resonator immersed in fluid, ii) determine the Young's (shear) modulus of prepared ultrathin film only from frequency response of the resonator with sputtered film, and iii) perform heavy analyte mass spectrometry by monitoring shift in frequency of just a single vibrational mode. The procedures required to estimate the Young's (shear) modulus of ultrathin film and the heavy analyte mass from observed changes in the resonant frequency caused by a phase transformation in SMA are developed and, afterward, validated using numerical simulations. The present results demonstrate the outstanding potential and capability of high frequency operating hybrid SMA-based nanomechanical resonators in sensing applications that can be rarely achieved by current nanomechanical resonator-based sensors.
Keywords: Young’s modulus; phase transformation; Q-factor; shape memory alloys; mass spectrometry; nanomechanics; resonator